DAMPAK KEBIJAKAN DIVIDEN, KEPEMILIKAN MANEJERIAL, DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Nuur, Harzuna Said; Fandiyanto, Randika; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Dividend distribution policy is a company's decision regarding how to distribute profits that have been obtained, whether to distribute to investors or to reinvest in the company. A consideration that companies need to take into account when distributing dividends is how much dividend will be paid to shareholders compared to the amount that will be reinvested in the company. At its core, dividends are a cash flow given to shareholders, but retained earnings are also an effective way to fund company growth. The aim of this research is to analyze and test "The Impact of Dividend Policy, Managerial Ownership, and Intellectual Capital on Company Value with Profitability as an Intervening Variable". This research is quantitative research. The population used in this research is 31 companies. Sampling technique used a purposive sampling technique, namely data was selected based on certain criteria that were in accordance with the research objectives. Data analysis and hypothesis testing in this research used the Structural Equation Method - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that leadership has a significant positive effect on job satisfaction, work motivation has a significant positive effect on job satisfaction, work discipline has a significant positive effect on job satisfaction, leadership has a negative but insignificant effect on performance, work motivation has a positive but insignificant effect on performance, work discipline has a negative but insignificant effect on performance, job satisfaction has a significant positive effect on performance. The results of the indirect effect hypothesis test show that the Leadership variable on performance through job satisfaction has a significant positive effect, motivation on performance through job satisfaction has a significant positive effect, and work discipline on performance through job satisfaction has a significant positive effect.